Excitation functions for fast-neutron induced reactions on zinc. (January 2023) - Liu, B.; Tian, G.; Han, R.; Shi, F.; Huang, Y.; Chen, Z.; Zhang, X.; Sun, H.; Tang, X.; Zhang, Z.; Luo, P.
Abstract: Cross sections of the 64 Zn(n, p) 64 Cu, nat Zn(n, x) 67 Cu, 66 Zn(n, 2n) 65 Zn and 70 Zn(n, 2n) 69 m Zn reactions have been measured by using the activation technique at 14.0 MeV neutron energy. The neutrons were produced via the 3 H(d, n) 4 He reaction. The present experimental data illustrated satisfactory agreement with most of the previously reported experimental data. Experimental data are compared with evaluated nuclear data of the CENDL-3.2, ENDF/B-VIII.0, JENDL-5, BROND-3.1 and JEFF-3.3 libraries. Besides, these excitation functions were calculated by using theoretical model of the TALYS-1.96 code from thresholds up to 20 MeV. A group set of parameters was obtained which better reproduce the experimental data than the default parameters. Highlights: Activation cross sections of neutron induced reactions on zinc were measured. Activation formula with changed neutron flux rate was applied. Reliability of the evaluated nuclear data libraries were verified. Excitation functions were calculated by using the TALYS-1.96 code with default and adjusted parameters.